Selective Area Hydrophobic Modification of Inkjet Head Plate for Reducing Diagonal Ink Ejection and Non-ejection. (October 2020) - Han, Kiduk; Son, Sanguk; Yong, Kijung
Highlights: A microcontact printing (μCP) was applied to enhance the uniformity of inkjet printing. Selective area superhydrophobic coating was processed on the head plate. A μCP effectively reduces diagonal ink ejection and non-ejection. A μCP reduces the frequency of the head plate care also. Abstract: When the inkjet printer jets inks, the nozzle of head plate is easily getting wet due to low surface energy of ink, high jetting frequency and high plate surface energy. As a result, non-ejection or diagonal ejection of ink occurs at the time of jetting, which causes non-uniform inkjet printing issues. To solve this problem, in current study, a selective hydrophobic coating of the inkjet head plate was applied using a microcontact printing (μCP) to enhance the uniformity of printing. Due to the characteristics of μCP, the hydrophobic self-assembled-monolayer was selectively deposited only on the surface of the head plate except the inside of the nozzle, which increases the contact angle of the inkjet head plate up to 105.45 ± 2.30°. This selective hydrophobic coating effectively decreases a jetting off-angle of the inkjet printer (Dimatix SG-1024) by ∼ 30 % while maintaining the same meniscus pressure and ink drop velocity as the unmodified conventional printer. The hydrophobic coating produced through this work has a facile regenerability, which is suitable for practical usage in inkjet printer. Furthermore, this method will increase the head life-time by reducing the frequency of the head plate care.